Pertanggungjawaban Pidana Terhadap Prajurit Tni Yang Menunggu Putusan Berkekuatan Hukum Tetap - Widijantoro, Setiawan (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2020)
Abstract— The purpose of this study is to examine the form of criminal liability for members of the TNI who carry out Military Criminal Acts and find out about the process of resolving military criminal cases against the TNI who are waiting for a court decision with permanent legal force. The research method used is a type of normative research with a conceptual approach, legislation, comparative and case approaches. Based on research results show that the form of criminal liability for TNI soldiers who commit crimes, namely: (a) The crime of desertion, can be sentenced to death if carried out by soldiers who crossed to the enemy during the war, and imprisonment if carried out in peace; (b) The crime of insubordination, can be sentenced to prison for more than 1 (one) year; (c) A criminal offense is absent, can be sentenced to imprisonment for more than 1 (one) year, but if the absent is not more than 3 (three) days can be disciplined. While the settlement starts from the investigation, examination until the decision based on the applicable regulations. Keywords—: Responsibility; TNI Soldiers; Military Criminal Society.